Evaluation of the dynamics of electrotensodynamometry indicators during the implementation of the physical therapy program for children aged 5–6 years with the consequences of hip dysplasia - Zviriaka, Oleksandr; Rudenko, Anna; Svierchkova, Olha (Фізична реабілітація та рекреаційно-оздоровчі технології, 2022)
Purpose: to investigate and evaluate the indicators of electrotensiodynamometry in the process of implementing a program of physical therapy for children aged 5–6 years with the consequences of hip dysplasia (HD). Material & Methods: 131 children were examined, from which two groups were subsequently formed: the HD group (n=68) - a group of children with the consequences of HD; comparison group (n=63) – healthy children. The HD group was divided into control (n=33) and main (n=35). To evaluate the results, the method of electrotension dynamometry of the thigh muscles was used. Results: there is an asymmetry in the development of the strength capacity of the muscles of the lower limbs (the tone of the adductor muscles exceeds the tone of the hip abductor muscles, there is an asymmetry in the muscle tone of the hip flexors and extensors when compared with an intact limb) in children with HD. A program of physical therapy (basic and variable component) for children 5-6 years old with the consequences of HD on the level of function and activity/participation of the ICF-CY was developed. The effectiveness of the program was confirmed by the dynamics of electrotensiodynamometry indicators, where the strength of the hip abductor muscles of the affected limb did not have statistically significant (p>0,05) differences (intact – 86,42±6,63, affected – 83,21±6,34), in contrast to the control group, where the parameters of the affected group were statistically significantly (p <0,05) higher (intact – 82,14±7,41, affected – 57,25±7,53). Conclusions: the dynamics of electrotensiodynamometry indicators of the thigh muscles during the implementation of the physical therapy program for children aged 5-6 years with the consequences of HD shows the advantages of the developed physical therapy program, which was tested in the main group. Positive changes were noted in the control group, which were determined by increasing indicators of the moment of strength of the thigh muscles of the affected limb, but they did not have a confirmed statistically significant (p>0.05) positive effect.